Nanoscale self-recovery of resistive switching in Ar+ irradiated TiO2−x films. (30th October 2017) - Barman, A; Saini, C P; Sarkar, P K; Das, D; Dhar, S; Singh, M; Sinha, A K; Kanjilal, D; Gupta, M; Phase, D M; Kanjilal, A
Abstract: Nanoscale evidence of self-recovery in resistive switching (RS) behavior was found in TiO2− x film by conductive atomic force microscopy when exposed to Ar + -ions above a threshold fluence of 1 × 10 16 ions cm −2 . This revealed an evolution and gradual disappearance of bipolar RS-loops, followed by reappearance with increasing number of voltage sweep. This was discussed in the realm of oxygen vacancy (OV) driven formation, dissolution and reformation of conducting filaments. The presence of OVs in ion-beam irradiated TiO2− x films was evidenced by decreasing trend of work function in scanning-Kelvin probe microscopy, and was further verified by x-ray absorption near edge spectroscopy at Ti and O- K edges.